MODELLING THE EFFECT OF SELECTED FACTORS ON ADOPTION OF OVER-THE-TOP SERVICES IN KENYA - Rono, Walter; Ogada, Kennedy; Mose, Thomas (International Journal of Technology and Systems, 2022)
Purpose: The goal of this research was to develop a model for the impact of several factors on OTT adoption in Kenya. Materials and Methods: This study employed an explanatory research technique. The target population for this study was limited to 23076 subscribers, who were the active subscribers of Viusasa as of December 2018. Simple random sampling was used to sample form the target population. Data collection was done through a structured questionnaire, which was both in soft and hard copy. Statistical package for social sciences (SPSS v25.0) was utilized to analyze the responses received from the questionnaire. The study generated and used averages, frequencies, and percentages to present the analysis. Results: The findings revealed that individual factors (Î²=0.326, p=0.000), technological factors (Î²=0.268, p=0.000), organizational factors (users) (Î²=0.166, p=0.000) and environmental factors (users) (Î²=0.270, p=0.000) have a positive and significant relationship with the adoption of OTTs in Kenya. Pay TV providers and broadcasting stations that are providing or purpose to provide OTT services to focus on the key individual factors that lead to the adoption of OTT services. Based on the multiple regression findings, the null hypotheses were rejected since the P values were less than 0.05 and thus, there is a significant effect individual factors, technological factors, organizational factors and environmental factors on the adoption of OTT services in Kenya is not statistically significant. Unique contribution to theory, practice and policy: The study findings indicate that the theory of diffusion is applicable to the study of factors influencing the adoption of OTT. Pay TV providers and broadcasting stations that were providing or purposed to provide OTT services are encouraged to focus on the key individual factors that lead to the adoption of OTT services. The understandings assisted on the providers improving their relationship with the users and have a bigger market even in terms of the customer base. Telecom operators in Kenya are encouraged to develop competitive OTT services to gain a competitive advantage over the present OTTs' players.